Nonparametric structural estimation of labor supply in the presence of censoring - Che-Yuan Liang (Uppsala University, Department of Economics, 2009)
This paper extends the nonparametric method to estimate labor supply developed by Blomquist and Newey (2002) to handle cases in which there are individuals who do not work. The method is then applied to married women in Sweden from 1973 to 1999. For 1999, I find an aggregate uncompensated wage elasticity around 1 and an aggregate income elasticity around -0.05. Furthermore, marginal tax rates are beyondthe net government revenue maximizing rates. Despite large labor supply effects, the dramatic evolution of the tax system can only explain a small share of the 58 percent rise in female labor supply during this period.
urn:nbn:se:uu:diva-103924
Keywords: C14; D31; H31; J22; 330; female labor supply; nonparametric estimation; nonlinear budget sets; tax revenues; Arbeitsangebot; Weibliche Arbeitskräfte; Steuereinnahmen; Nichtparametrisches Verfahren; Schätzung; Schweden